Taekwondo back kick kinematics of elite and youth athletes - Detjareny, T.; Limroongreungrat, W.; Sinphurmsukskul, O.; Pinthong, M. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to analyze taekwondo back kick kinematics of elite and youth athletes. The athletes were instructed to perform basic back kick ats the target with their dominant leg. 3D motion analysis system was captured three back kicks at the sampling rate of 100 Hz. Response time was also recorded. The Mann-Whitney U test did not reveal significant differences of selected kinematics and temporal variables of back kick between two groups. Both athlete groups show similar kicking pattern. Peak linear velocity occurs prior to the impact. Peak kicking velocity should occur near the impact. Nevertheless, this study only investigated static simple back kick. Future research should investigate different types of back kick.